2003
DOI: 10.1248/bpb.26.1365
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal Concentration of Hydroquinone after Application of Hydroquinone Ointments Is Higher than Its Cytotoxic Concentration

Abstract: Ointments of the skin depigmentation agent hydroquinone (HQ) have been prepared by extemporaneous nonsterile compounding in our hospital. The HQ ointments were highly effective in the treatment of various types of skin pigmentations; however, various problems have emerged including chromatic aberration of the ointments, a relatively large variability of efficacy, and mild topical side effects including irritation. In this paper, the cytotoxicity of HQ was assessed in vitro using rat skin fibroblasts as the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…30,31 The cytotoxic and mutagenic potentials of hydroquinone have caused the drug regulatory authorities of several countries to ban the use of this compound as a depigmenting agent. The cytotoxicity of hydroquinone is not specific for melanocytes, and other epidermal cells, such as keratinocytes, may also be affected.…”
Section: Cysteamine Placebomentioning
confidence: 99%
“…30,31 The cytotoxic and mutagenic potentials of hydroquinone have caused the drug regulatory authorities of several countries to ban the use of this compound as a depigmenting agent. The cytotoxicity of hydroquinone is not specific for melanocytes, and other epidermal cells, such as keratinocytes, may also be affected.…”
Section: Cysteamine Placebomentioning
confidence: 99%
“…Furthermore, our in vivo studies demonstrated that intraplantar injection of HQ at a concentration range of 1 to 30 mM can readily produce both acute pain and persistent mechanical hyperalgesia in mice. This concentration range is much lower than the concentration of HQ found in stratum corneum and epidermis plus dermis tissue (358 and 51.7 mM, respectively) when 5% clinically used HQ ointment is applied on the skin 26 . Therefore, it is quite likely that topically applied HQ ointment in patients, containing much higher amounts of HQ, will activate TRPA1 and cause irritation and pain.…”
Section: Discussionmentioning
confidence: 69%
“…A previous study investigated the intradermal concentration of clinically used HQ (5.0%) after its permeation using rat skin 26 . In that study, it was reported that the intradermal concentrations at 2 h after application of the HQ ointments were 358 mM in stratum corneum and 51.7 mM in epidermis plus dermis tissue 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In low concentrations (<10 µ M ), HQ shows a melanogenesis-inhibiting effect, while in higher concentrations it mainly acts as a melanocytotoxic agent [1]. The depigmenting effect of HQ products on human skin, however, is perhaps solely due to its melanocytotoxic potential, as the concentration of HQ delivered into the dermis by such products is several folds higher than the dosage required for its cytotoxic effects [4]. The cytotoxicity of HQ is not highly specific for melanocytes, and other cells, such as keratinocytes, can also be affected [1, 5].…”
Section: Discussionmentioning
confidence: 99%